Evaluation of Highway-pilot Function Based on FMEA Safety Analysis - Bényei, Ádám; Vida, Gabor; Pintér, Krisztián; Szalay, Zsolt; Ágoston, György (Periodica Polytechnica Transportation Engineering, 2020)
Cybersecurity is becoming more and more relevant. Autonomous vehicles handle large amounts of data and can connect to more and more existing devices, smartphones, tablets, or even other cars and systems. This poses the risk of unauthorized access to data. Theoretically cars have separate computer units, operate in isolation, and are not connected, so there is less possibility to be attacked. However if the vehicles are interconnected, hackers can have easier access to personal data. They can get information about the location of the car owner, their typical trips, and, for example, allow an intruder to know when the tracked person is not at home. Furthermore it can also be happened that the vehicle operation is maliciously disturbed, which can result in a security risk for the passengers. In extreme cases, computer terrorist attacks can also be prepared - large-scale interventions on roads can lead to chaos across a region or country. In accordance with the introduced threats, it is a crucial objective of this research to indicate specific methods, which can help the industry to evaluate and prepare for these kinds of attacks in a proper way.